Functional Health Literacy and Associated Factors in Cancer Patients at a University Hospital - Paes, Nayara Fernandes (2024)
Introduction: Functional health literacy (FHL) is an individual’s ability to comprehend health information, influencing the engagement in preventive practices, early disease detection, management of chronic illnesses, andaccess to healthcare services. Objective: To identify FHL levels and associated variables in patients undergoing intravenous antineoplastic outpatient treatment. Method: Between July 2020 and March 2021, 116 patients undergoing intravenous antineoplastic therapy respondedto a sociodemographic and health questionnaire, along with an FHL assessment tool. The dependent variable in this study was the level of LFS (Life Satisfaction) of the interviewees, while the independent variables were their sociodemographic, health, and professional-patient relationship characteristics. Results: Around 54% presented inadequate or borderline FHL. The analysis revealed higher odds of limited FHL among older patients (OR 1.05), those receiving chemotherapy for the first time (OR 4.57), and individuals with education up to elementary school (OR 23.42). Conclusion: The study highlights priority groups that require specialized attention and detailed guidance to improve care, especially patients at the beginning of cancer treatment.